Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2174/13816128113196660746
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Endothelial NO Synthase Uncoupling

Abstract: Nitric oxide (NO) is a gaseous signaling molecule and effector in various biological processes. In mammalian cells, NO is produced by a family of NO synthases (NOS). Three NOS isoforms have been identified as: neuronal NOS (nNOS), inducible NOS (iNOS), and endothelial NOS (eNOS). In addition to NO, NOS also produces superoxide anion. This phenomenon is named NOS uncoupling as superoxide generation mainly occurs when NOS is not coupled with its cofactor or substrate. nNOS was first found to produce superoxide u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 0 publications
0
69
0
6
Order By: Relevance
“…Induction of COX-2 and iNOS by inflammatory and apoptotic stimuli causes generation of reactive oxygen species and reduced nitric oxide availability. 23,24 Furthermore, adhesion molecules are important mediators of the inflammatory milieu triggering monocyte infiltration and foam cell formation. 15,25 Our findings strongly suggest that histone methyltransferase Set7 is critically involved in the pathophysiology of vascular dysfunction in patients with diabetes mellitus ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of COX-2 and iNOS by inflammatory and apoptotic stimuli causes generation of reactive oxygen species and reduced nitric oxide availability. 23,24 Furthermore, adhesion molecules are important mediators of the inflammatory milieu triggering monocyte infiltration and foam cell formation. 15,25 Our findings strongly suggest that histone methyltransferase Set7 is critically involved in the pathophysiology of vascular dysfunction in patients with diabetes mellitus ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…The source of the superoxide may be NOS itself or superoxide generated from NOX or cytosolic xanthine oxidase, peroxisomal oxidases, or endoplasmic reticular oxidases. When NOS is uncoupled with its cofactor tetrahydrobiopterin or its substrate, arginine, there can be a massive increase in superoxide formation (36). Overproduction of NOS isoforms as a contributor to diabetic neuropathy has also been recently demonstrated (1) (Fig.…”
Section: Figmentioning
confidence: 95%
“…22 NADPH oxidase and NOS uncoupling because of l-arginine deficiency contribute to superoxide generation in endothelial cells. 23 Treating human endothelial cells with l-arginine, Sankaralingam et al 10 demonstrated that in the presence of superoxide formation, l-arginine supplementation led to formation of peroxynitrite, which has been shown to be increased in the vasculature of women with preeclampsia. 24 In contrast, l-arginine supplementation after inhibition of oxidative stress did not result in peroxynitrite formation, 10 indicating that the oxidant status of the maternal environment may determine the efficacy of certain therapeutic interventions.…”
Section: Endothelium-derived Vasodilatorsmentioning
confidence: 99%